Introduction to Experimental Music “Nyelah Ngunjar” | Pengantar Musik Eksperimental “Nyelah Ngunjar” - I Putu Wahyu Andika; I Ketut Muryana (GHURNITA: Jurnal Seni Karawitan, 2022)
Experimental musical composition inspired by traditional musical instruments in Batuan Village, Sukawati District, Gianyar Regency. Both instruments are packaged in a new way by being combined with string instruments including Violin, Cello, Erhu, and Rebab. With the various instruments specified, Nyelah Ngunjar's work was formed or claimed to be experimental music. This is due to the need for ideas to explore instruments both in terms of timbre and instrument functionality by getting a touch of technology (delay effect) in the Ableton Live 10 Suite application. The structure used in Nyelah Ngunjar's work uses 3 structures including part 1, part 2, and part 3, each part has a different direction and purpose. The method used in Nyelah Ngunjar's work uses the Roger Session method which includes inspiration (ideas, media, references), conception (designing ideas, compiling ideas), execution (making ideas come true). The total duration of Nyelah Ngunjar's work is 11 minutes. This work is expected to provide positive benefits for all related components and can add insight and reference for the public to the experimental musical works that have been created. Keywords: Nyelah Ngunjar, experimental composition, genggong and gambuh